Long Non-coding RNAs Involved in Metabolic Alterations in Breast and Prostate Cancers - Kamada, Shuhei; Takeiwa, Toshihiko; Ikeda, Kazuhiro; Horie-Inoue, Kuniko; Inoue, Satoshi (Frontiers in Oncology, 2020)
Breast and prostate cancers are the most prevalent cancers in females and males, respectively. These cancers exhibit sex hormone dependence and thus, hormonal therapies are used to treat these cancers. However, acquired resistance to hormone therapies is a major clinical problem. In addition, certain portions of these cancers initially exhibit hormone-independence due to the absence of sex hormone receptors. Therefore, precise and profound understanding of the cancer pathophysiology is required to develop novel clinical strategies against breast and prostate cancers. Metabolic reprogramming is currently recognized as one of the hallmarks of cancer, as exemplified by the alteration of glucose metabolism, oxidative phosphorylation, and lipid metabolism. Dysregulation of metabolic enzymes and their regulators such as kinases, transcription factors, and other signaling molecules contributes to metabolic alteration in cancer. Moreover, accumulating lines of evidence reveal that long noncoding RNAs (lncRNAs) regulate cancer development and progression by modulating metabolism. Understanding the mechanism and function of lncRNAs associated with cancer-specific metabolic alteration will therefore provide new knowledge for cancer diagnosis and treatment. This review provides an overview of recent studies regarding the role of lncRNAs in metabolism in breast and prostate cancers, with a focus on both sex hormone-dependent and -independent pathways.